Nursing student’s knowledge about understanding and prevention of needle stick injury - Ledinski Fičko, Sanja (Array, 2020)
Introduction. Needle stick injury (NSI) is an occupational health and safety issue. Nursing students are prone to NSI due to lack of experience with handling needles and sharps. Aim. To determine the level of knowledge about the prevention of NSI and examine the level of knowledge about the post-exposure procedure and the students’ understanding of NSI. Methods. The study was conducted in 2017 at the University of Applied Health Sciences in Zagreb. The participants were nursing students from all regions of Croatia. The data was collected using a questionnaire containing 17 questions specifically designed for this study. One question had three subquestions and one had five subquestions regarding the knowledge of how to react if a needle stick injury occurs. The participants also responded to a questionnaire on their socio-demographic data. Results. The study included 149 students. The results show that 16 students have experienced NSI. A statistically significant difference was observed among students who have finished a secondary medical school in the answers about post-NSI interventions and in answers to the question of whether the needle should be recapped. The respondents from medical schools answered correctly. A statistically significant difference was observed among students from non-medical secondary schools in the answers about education on post-exposition procedures and in the answers about necessary action following a needle stick injury. The respondents from non-medical secondary schools had higher scores. Conclusion. The results of this study can be used to establish appropriate education strategies, increase the awareness of needle stick injuries and minimize the occurrence of these injuries among nursing students in Croatia.